Drawing on the Implications of Indonesia's Founding Father's Transformative Theological Practice for the Development of Inclusive Education for Students - Suparjo (Edukasia, 2022)
This study analyzes the inclusive theology adopted by the Indonesian founding fathers in promoting Pancasila as an indigenous global theology for Indonesia. During the early days of the formation of the state and nation of Indonesia, it is evident that the founding fathers embraced inclusive theology. This paper aims to analyze the inclusive theology of the Indonesian founding fathers, highlighting their role in promoting Pancasila, particularly its first pillar of Ketuhanan Yang Maha Esa (the oneness of God), as an indigenous global theology for Indonesia. Moreover, their inclusive approach serves as an exemplary model of global theology for future Indonesian Muslim generations. Using a qualitative approach, this study analyzes historical documents, such as the debates and discussions in BPUPKI and PPKI, as well as religious texts like the Quran and Hadith. The findings demonstrate that the Indonesian founding fathers practiced inclusive theology by integrating their religious identity with the national identity of Indonesia. By adopting inclusive perspectives and drawing from the rich heritage of inclusive thought in Islamic civilization, their approach to theology provides valuable insights for fostering pluralism and unity within Indonesian society.